Inovasi Pengelolaan Pusat Kegiatan Belajar Masyarakat (PKBM) : Peningkatan Kualitas Kelembagaan PKBM di Kabupaten Bandung - Ansori Ansori; Dinno Mulyono; Tiffany Estherlita; Furqon Nulhakim; Dadang Hermawan (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2024)
The Community Learning Center (PKBM) plays a vital role in providing educational access to communities not reached by formal institutions. However, challenges in managing and institutional management of PKBM often affect the quality of educational services. This research aims to enhance the institutional management quality of PKBM in Bandung Regency through a workshop titled "Innovation in PKBM Management: Efforts to Improve Institutional Management Quality at the District Level in Bandung Regency." The research method involves conducting workshops with PKBM managers from various areas in Bandung Regency. The workshop content includes innovative strategies in PKBM management, understanding institutional management, and case studies to reinforce concept application. The results show an improvement in understanding and skills among PKBM managers in effectively managing their institutions. The workshop also identifies several innovations that can be applied to enhance the quality of educational services at PKBM. In conclusion, this workshop activity successfully contributes positively to improving the institutional management quality of PKBM at the district level in Bandung Regency.